Mental disability, violence, and future dangerousness : myths behind the presumption of guilt - Parry, John, 1948- (Rowman and Littlefield Publishers, Incorporated, 2013)
Using a multi-disciplinary approach, this book documents and explains how, when and why adults and children with mental disabilities-including those with sexual disorders- who are perceived to be a future danger to others, the community, or themselves have become the most stigmatized, abused, and mistreated group in America, and what should be done to correct the resulting injustices. The author identifies and analyzes the key factors that should be understood when lawyers, judges, mental health professionals, policymakers, legislators, advocates, forensic experts, professors and their students consider the legal, treatment and policy decisions that affect this highly stigmatized group of people.